Russia 2019 - Akhmetova, Elmira (Brill, 2019)
This book chapter is a report for 2019 on the status of Islam and Muslims in the Russian Federation. Issues like the public debate on Islam and Muslims, Muslims' rights, activities of Muslim organisations are covered.